ANALISIS BOLLARD PULL TEST PADA KAPAL TUG BOAT GT.117 DENGAN SISTEM PROPULSI FIXED PITCH PROPELLER (FPP) - Muhammad Arsyad; Andi Rachmianty (Jurnal Teknologi Dan Riset Terapan (JATRA), 2026)
Bollard Pull Test is a standard procedure to measure the static towing capacity of a tug boat under full engine load. This study analyzes the Bollard Pull Test results of tug boat GT.117, equipped with two 6HA2M-WDT main engines producing a combined power of 596 kW, and a propulsion system consisting of two sets of four-blade Fixed Pitch Propellers (FPP). The test was conducted on October 2, 2025, for 10 minutes at 100% engine load (RPM = 1,850), generating 120 data points. Descriptive statistical analysis yields a mean bollard pull of 8.567 tons, standard deviation of 0.335 tons, maximum of 9.321 tons, minimum of 7.657 tons, and a coefficient of variation of 3.91%, indicating good test stability. Comparison with theoretical values based on actuator disk theory yields a total theoretical thrust of 8.967 tons, giving an actual-to-theoretical ratio of 95.6%. After wind resistance correction of 0.018 tons, the corrected bollard pull is 8.585 tons. Test results comply with Bureau Veritas (BV) classification requirements and port operational standards. Water depth factor h⁄T=5.85) and wind speed of 8 knots are assessed to have no significant effect on test validity. This study contributes to Indonesian naval architecture literature by providing a comprehensive quantitative analysis of tug boat propulsion performance based on standardized field test data.